Optimisation of metallic bismuth nanoparticle supported Pt-Bi(x%)/C hybrid electrocatalyst for cost effective and efficient hydrogen production in alkaline media - Dokhe, Revati; Ugale, Atul; Dube, Onkar; Varpe, Vaibhav; Galave, Chaitanya; Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Kumar, Ajay; Husale, Sudhir; Natu, Varun; Shevate, Rahul; et al. (International Journal of Hydrogen Energy, 2025)
The present study employed a simple mechanochemical method followed by 24-h ultrasonication to synthesize oxide-free metallic bismuth (Bi) nanoparticles. This was further used to synthesize a Pt-Bi(x%)/C (NC-x) hybrid electrocatalyst for the hydrogen evolution reaction in alkaline media. X-ray photoelectron spectroscopy and contact angle measurements reveal, Bi modifies the electronic structure and surface morphology of the Pt/C electrocatalyst, thus enhancing reaction kinetics and active site availability. The relative three-electrode study reveals that optimised NC-20 electrocatalyst reduces the overpotentials by 10.44 % and enhances the current density by 53 % compared to commercial Pt/C. The practical applicability of the NC-20 electrocatalyst was studied with the 13 cm2 single cell anion exchange membrane electrolyser. The catalyst demonstrates promising performance where the current density of NC-20//IrO2 relatively increases by 22.6 % compared to standard Pt/ C//IrO2, and shows continuous production and stable performance when monitored for 30 h.
Keywords: AEM; Bismuth nanoparticles; electrocatalyst; Full cell electrolysis; hydrogen evolution reaction; water electrolysis

Effect of surface engineering of nickel foam on hydrogen evolution reaction: a comprehensive study for high throughput - Dokhe, Revati; Ugale, Atul; Virole, Vishal; Dube, Onkar; Varpe, Vaibhav; Galave, Chaitanya; Hattale, Gangadhar; Kadam, Rutuja; Kumar, Ajay; Husale, Sudhir; Natu, Varun; Shevate, Rahul; et al. (Advanced Engineering Materials, 2026)
Interfacial engineering plays a key role in enhancing the performance of electrocatalysts for Hydrogen evolution reaction (HER). Surface modification of porous transport layer (PTL) enhances the active catalytic sites, improves membrane electrode interfacial contact, and facilitates efficient mass transport during water electrolysis. In this study, we report a simple, cost and time effective mechanical bilateral polishing technique to engineer the surface of nickel foam (NF) for efficient HER. The structural and surface analysis, using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS), contact angle measurement, and 3D X-ray CT, confirms the effective removal of unwanted dendritic microstructures, enhanced wettability, and a more uniform catalyst coating, leading to increased active catalytic sites. Contact pressure analysis shows improved interfacial contact between the engineered NF, membrane and monopolar/bipolar plates. The relative electrochemical half-cell measurements show that the Pt/C coated engineered NF delivers a significantly higher current density of -552.55 mA cm-2 compared to -357.85 mA cm-2 for the Pt/C coated bare NF at lower overpotentials. In a 13 cm2 AEM electrolyzer cell, the Pt/C@Eng // RuO2@Eng configuration demonstrates a superior current density of 283.9 mA cm-2 compared to 156.63 mA cm-2 for the bare Pt/C // RuO2 configuration. A stability test of over 155 h shows robust durability. This work highlights the effectiveness of a simple surface engineering approach for NF in improving the HER.
Keywords: electrode surface coating; electrode surface engineering; electrolyzer performance testing; engineered nickel foam; hydrogen production; Nickel foam; water electrolysis